Peripheral and segmental spinal abnormalities of median and ulnar somatosensory evoked potentials in Hirayama's disease. Issue 5 (1st May 2003) - Polo, A; Dossi, M Curro'; Fiaschi, A; Zanette, G P; Rizzuto, N
Abstract : Objectives: To investigate the origin of juvenile muscle atrophy of the upper limbs (Hirayama's disease, a type of cervical myelopathy of unknown origin). Subjects: Eight male patients were studied; data from 10 normal men were used as control. Methods: Median and ulnar nerve somatosensory evoked potentials (SEP) were recorded. Brachial plexus potentials at Erb's point (EP), dorsal horn responses (N13), and subcortical (P14) and cortical potentials (N20) were evaluated. Tibial nerve SEP and motor evoked potentials (MEP) were also recorded from scalp and spinal sites to assess posterior column and pyramidal tract conduction, respectively. Results: The most important SEP findings were: a very substantial attenuation of both the EP potentials and the N13 spinal responses; normal amplitude of the scalp N20; and normal latency of the individual peaks (EP-N9-N13-P14-N20). Although both nerves were involved, abnormalities in response to median nerve stimulation were more significant than those in response to ulnar nerve stimulation. There was little correlation between the degree of alterations observed and the clinical state. Latencies of both spinal and cortical potentials were normal following tibial nerve stimulation. The mean latency of cervical MEP and the central conduction time from the thenar eminence were slightly but significantly longer in patients than in controls. Conclusions: The findings support the hypothesis that this disease, which is clinically defined as a focal spinal muscle atrophy of the upper limb, may also involve the sensory system; if traumatic injury caused by stretching plays a role in the pathogenesis, the damage cannot be confined to the anterior horn of the spinal cord.